1993
DOI: 10.21000/jasmr93010385
|View full text |Cite
|
Sign up to set email alerts
|

Standing Crop Biomass and Cover on Amended Coarse Taconite Iron Ore Tailings

Abstract: Abstract.The purpose for reclaiming mineral related mining waste sites is to stabilize them to prevent wastes from being moved by wind and water. Principal methods used to stabilize mining waste are physical, chemical, and vegetative. The ecological approach used to research stabilization of northern Minnesota coarse taconite tailing is a combination of physical and vegetative stabilization techniques. The Bureau of Mines has implemented a series of unbalanced factorial experiments on two sites based on amendm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…The highest rate (89.6 Mg/ha) had significantly greater percent cover and biomass than any of the other treatments. Percent cover and biomass compare closely after 2 growing seasons with results from a study (Norland et al 1992(Norland et al , 1993) completed earlier using similar application rates of MSW compost. Subsequent findings (Norland et al 1994) showed that the 90% cover standard was achieved after 4 seasons.…”
Section: Ground Coversupporting
confidence: 70%
See 1 more Smart Citation
“…The highest rate (89.6 Mg/ha) had significantly greater percent cover and biomass than any of the other treatments. Percent cover and biomass compare closely after 2 growing seasons with results from a study (Norland et al 1992(Norland et al , 1993) completed earlier using similar application rates of MSW compost. Subsequent findings (Norland et al 1994) showed that the 90% cover standard was achieved after 4 seasons.…”
Section: Ground Coversupporting
confidence: 70%
“…In a companion study (Melchert et al 1994), MSW compost was applied to a tailing site to examine impacts on water quality and runoff. In recent years other studies have been initiated by the MDNR and the U.S. Bureau of Mines, studying the usefulness of MSW compost as a soil amendment for revegetating coarse !aconite tailing (Norland et al 1991(Norland et al , 1992(Norland et al , 1993. The objective of this paper is to assess tree growth and trace metal concentrations in leaf tissue for trees planted in coarse tailing plots treated with four rates of MSW compost.…”
Section: Introductionmentioning
confidence: 99%
“…Percent cover was measured in each plot with a cover point projection sampler and biomass was measured in two to three 0.1 m 2 sub plots. (Additional detail on plot construction and methods can be found in Norland et al, 1991, 1993, 1995, and McCarthy et al, 1995.…”
Section: Small Plots /Usx Evtac}mentioning
confidence: 99%
“…The U.S. Bureau of Mines (USBM) has established research plots on coarse tailings using organic amendments at several locations in northeastern Minnesota, including Eveleth Mines. The research program of the USBM was established because standard methods of revegetation have not been successful in vegetating coarse taconite tailings (Norland 1993;Norland, Veith, and Dewar 1993;Melchert et al 1994). Many darns and dikes constructed using coarse tailings have only attained a 40 percent to 60 percent plant cover after three years (Shetron and Duffeck 1970;Dewar 1987).…”
Section: Introductionmentioning
confidence: 99%